Władze polskie wobec problemu roszczeń finansowych w stosunkach z Włochami w latach 1945–1956 - Jarosz, Dariusz; Pasztor, Maria (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2013)
The sketch is an attempt to present the main financial problems in the Polish-Italian relations from 1945 to 1956. It is based primarily on sources stored in Central Archives of Modern Records and Archives of the Ministry of Foreign Affairs in Warsaw. The study showed that the main purpose of the Polish authorities was to avoid having to pay the pre-war debts to Italy, and compensation resulting from the adoption of the law on nationalization of industry, from 3 January 1946. For this purpose it was intended to take advantage of the provisions of a peace treaty with Italy, which was ratified by Poland in 1947. Polish-Italian talks on this subject led to a compromise: The Geneva Protocol was initialed on June 3, 1949, in which the Italian government renounced the pre-war debts in exchange for the surrender of the Polish government’s war reparations from Italy. As a result of the increased tension in the international situation, the protocol does not come into force, which increased the difficulties in Polish-Italian trade cooperation.